2019
DOI: 10.1073/pnas.1817757116
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the Neisseria meningitidis PilF ATPase provoke type IV pilus disassembly

Abstract: Despite the availability of antibiotics and vaccines, Neisseria meningitidis remains a major cause of meningitis and sepsis in humans. Due to its extracellular lifestyle, bacterial adhesion to host cells constitutes an attractive therapeutic target. Here, we present a high-throughput microscopy-based approach that allowed the identification of compounds able to decrease type IV pilus-mediated interaction of bacteria with endothelial cells in the absence of bacterial or host cell toxicity. Compounds specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 29 publications
1
27
1
1
Order By: Relevance
“…Targeting the nucleotide-binding site or packing-unit interface to inhibit ATPase activity in T4P-like systems may have therapeutic value as these systems play a major role in virulence for many pathogens. Indeed, there are two recent reports of small-molecule inhibitors of the Neisseria meningitidis T4aP that target pilus polymerization and depolymerization dynamics to reduce virulence 41,42 . One of these drugs targets PilB directly 41 , although whether this drug binds the nucleotide-binding site or packing-unit interface is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting the nucleotide-binding site or packing-unit interface to inhibit ATPase activity in T4P-like systems may have therapeutic value as these systems play a major role in virulence for many pathogens. Indeed, there are two recent reports of small-molecule inhibitors of the Neisseria meningitidis T4aP that target pilus polymerization and depolymerization dynamics to reduce virulence 41,42 . One of these drugs targets PilB directly 41 , although whether this drug binds the nucleotide-binding site or packing-unit interface is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…Coincidentally, P4MP4 affected N. meningitidis aggregation and T4P in a manner resembling that of phenothiazines despite their different routes of discovery. Biochemical studies in this investigation pointed to PilF, the PilB equivalent in the N. meningitidis T4P system, as the potential target of P4MP4 instead of the Na 1 -NQR complex (30). It should be emphasized that the T4PM was not specifically targeted by the antiaggregation (29) or the antiadhesion (30) assays in either case for the discovery of phenothiazines or P4MP4.…”
mentioning
confidence: 82%
“…Two recent studies have identified inhibitors of neisserial tfp. The first inhibitor, referred to as compound B in the publication, was identified through a phenotypic screen and successfully prevented the adherence and formation of N. meningitidis microcolonies on the human umbilical vein endothelial cell surface [ 181 ]. Cellular and in vitro experiments showed that compound B could inhibit the PilF ATPase enzymatic activity resulting in lowered surface expression levels of tfp.…”
Section: Gonococcal Virulence Factors As Targets For Inhibitor Desmentioning
confidence: 99%
“…The effects of both compounds on piliation were fast acting, reflecting the rapid dynamics of the tfp [ 181 , 182 ]. Additionally, both studies showed that although these compounds were initially designed to inhibit N. meningitidis , they are also effective on other Gram-negative tfp-expressing bacterial pathogens such as N. gonorrhoeae and P. aeruginosa .…”
Section: Gonococcal Virulence Factors As Targets For Inhibitor Desmentioning
confidence: 99%